Pengaruh Penerapan Model Pembelajaran RBL Terhadap Kreativitas Belajar Siswa Kelas XI IPS Mata Pelajaran Ekonomi Di SMAN 2 Muaro Jambi - Oktavia, Dina Dwi; Yudha, Redi Indra (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to determine the effect of applying conventional learning methods and the RBL learning model in increasing the learning creativity of class XI IPS students in economics subjects at SMAN 2 Muaro Jambi. The research design that will be carried out in this research is a quasi-experimental research with a pre-test – post-test control group design model with one type of treatment. The results of the research show that there are differences in the influence of the conventional learning model and the RBL learning model on the creativity of class XI IPS students. Students who learn using the RBL learning model obtain the best creative learning abilities.